Thermal Behavior and Kinetic of Degradation of PVA and PVA/CS/AL Blend (Sainteknol : Jurnal Sains dan Teknologi, 2023)
Studying thermal behavior, especially regarding the kinetics of the degradation of materials has attracted attention in this recent years because it can provide information about the stability of materials in various conditions and how the mechanism of material degradation. In this research, the thermal behavior and kinetics of thermal degradation of polyvinyl alcohol (PVA) and polyvinyl alcohol (PVA)/cassava starch (CS)/alkaline lignin (AL) with glycerol as a plasticizer were investigated and compared by the thermogravimetric analyzer. The test was carried out for samples under non-isothermal conditions in nitrogen at a single heating rate of 10 °C/min. The activation energies were calculated using Coats-Redfern, Broido, and Horowitz-Metzger methods. The results showed that PVA/0 and PVA/CS/AL had four decomposition steps with the main degradation of PVA/0 and PVA/CS/AL in the second and third decomposition steps. The first degradation of PVA/0 and PVA/CS/AL occurred at 125 °C - 270 °C with a decomposed mass of 35.94%, and 135 °C – 250 °C with a decomposed mass of 31.84%, respectively. The second degradation of PVA/0 and PVA/CS/AL was at  270 °C - 385 °C with a decomposed mass of 40.33%  and 250 °C – 395 °C with a decomposed mass of 38.62%. The values of activation energies using Coats-Redfern, Broido, and Horowitz Metger methods of PVA/0 were 57.08 KJ/mol, 64.82 KJ/mol, and 70.57 KJ/mol, respectively. The values of activation energies using Coats-Redfern, Broido, and Horowitz Metger methods of PVA/CS/AL were 74.49 KJ/mol, 82.17 KJ/mol, and 95.65 KJ/mol, respectively. The lower activation energy indicates that degradation reactions occur more easily. PVA/CS/AL has slightly better thermal stability than PVA/0.